Peran Badan Amil Zakat Nasional (Baznas) dalam Pemberdayaan Ekonomi Masyarakat (analisis pengembangan Ekonomi Islam) - Mashur Mashur; Dedi Riswandi; Ahmad Sibawaihi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
potential for the development and welfare of the community's economic life. It is just, This potential must be managed professionally in order to achieve the goal of zakat for development  Islamic economics institutionally.  Zakat as an important aspect in economics is best when approached from the scientific and economic aspects institutionally can be a solution to alleviating poverty because it plays a role in  community empowerment, especially the poor, the poor and others. The Baznas institution as zakat manager becomes the object of this research so that this research qualitative. Interviews and observations were carried out  as a method for researchers to obtain data using the approach  qualitative. Based on the research, the researchers found that Baznas contributed significantly community empowerment through various programs that have been and are being implemented in various fields. Provision of working capital, capital or commercial equipment, capital agricultural seeds, animal husbandry capital for mustahik and others. Other help not only in the health sector, but also in education, humanity and others. All forms of assistance received by the community to meet the needs of life, improve the standard of living socio-economic life, fostering the spirit of mutual help, independence and others.  The Baznas assistance program is part of the institution's education to the community. hope, public awareness to be generous, obey the command of tithing enhancement.